Physical, Chemical, and Microbiological Characteristics of Ronto During Storage - Rita Khairina; Muhammad Nur Cahyanto; Tyas Utami; Sri Rahardjo (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2016)
AbstractThe purpose of this study was to determine the physical, chemical, and microbiological changes of ronto during storage at room and cold temperatures. Ronto was prepared by mixing fresh shrimp, salt, and rice with a ratio of 7 : 1 : 2 and fermented in a closed container for 14 days. Ronto produced was stored at room and cold (5oC) temperatures. Samples were withdrawn every 4 weeks and analyzed for its physical, chemical, and microbiological characteristics. The characteristic changes of ronto stored at low temperature were generally slower than those at room temperature. The changes in colour, viscosity, acidity, total volatile bases, and microbial counts were lower in ronto kept at 5oC compared to those in ronto kept at room temperature. The colour of ronto stored at low temperature remained red after 20 weeks, whereas the colour of ronto kept at room temperature turned brownish after 20 weeks.